THE EFFECT OF AUDIT FEES, AUDIT TENURE AND AUDIT COMMITTEE ON AUDIT QUALITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Amar Masruri; Ruruh Dyatmiko (International Research of Multidisciplinary Analysis, 2023)
This study aims to analyze the effect of audit fees, audit tenure and audit committees on audit quality in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used random sampling to obtain 17 companies listed on the Indonesia Stock Exchange in 2016-2020 or other words 85 samples were used in the study. This study uses panel data regression using E-views 12 software. The results show that audit fees, audit tenure and audit committees significantly affect audit quality. Partially, audit fees, audit tenure and audit committee have no significant effect on audit quality. Simultaneously audit fee, audit tenure and audit committee significantly affect audit quality